PENERAPAN ASPEK SPIRITUALITAS-RELIGIUSITAS DALAM KEPUTUSAN BEROBAT DI RUMAH SAKIT ISLAM - Anton Bawono (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2011)
This research is trying to observe spirituality-religiousity aspect through marketing mix that influences the patients to choose Islamic hospital. By applying non-profitability sampling in which data is collected through questionaire given to the patients in Rumah Sakit Islam KalimasadaYogyakarta. The finding on statistical and classical assumption show thatspirituality-religiousity aspect is the secondary aspect in making thedecision to choose Islamic hospital. So that this aspect play an importantrole for health organization to compete in health services.